Imaging the Messier Objects Remotely from Your Laptop - Adam, Len (The Patrick Moore Practical Astronomy Series,, 2018)
This is a guide for anyone interested in practical astronomy but intimidated by the idea of investing in a telescope. It explores the world of remote observing, which requires nothing more than a laptop and an Internet connection. The book aims to make readers comfortable navigating the plethora of online equipment at their disposal and to show that a challenge like imaging the Messier objects can be fun, simple, and achievable for all. In this text, all 110 Messier objects are discussed, each one remotely imaged with clear instructions on what telescope and camera combinations give the best results. Common astronomical phrases and units are all explained and illustrated to help newcomers get a grasp of terminology. Tidbits of history and quotes from Messier and other astronomers round out this beginner-friendly read, which also features a handy Quick Reference Image Library.